Are early and late rate of force development differently influenced by fast-velocity resistance training? - de Oliveira, Felipe B.D. [UNESP]; Rizatto, Guilherme F. [UNESP]; Denadai, Benedito S. [UNESP] (Wiley, 2013)
This study examined the effect of fast-velocity concentric isokinetic resistance training (FV) on the rate of force development (RFD) at early (<100 ms) and late phases (>100 ms) of rising muscle force. Nine men participated in a 6-week resistance training intervention for the lower body, and nine matched subjects participated as controls (CON). During concentric isokinetic (180°s-1) knee extension training, subjects were instructed to do each contraction 'as fast and forcefully as possible'. Maximal muscle strength (MVC) and RFD (0-10, 0-20, ..., 0-250 ms from the onset of contraction) were measured during maximal voluntary isometric contraction of the knee extensors (KE). There were no significant changes in MVC of KE in both groups after intervention (FV = 314·2 ± 101·1 versus 338·7 ± 88·0 N{bullet operator}m, P>0·05; CON = 293·3 ± 94·8 versus 280·0 ± 72·2 N{bullet operator}m, P>0·05). The RFD increased 39-71% at time intervals up to 90 ms from the onset of the contraction (P<0·05), whereas no change occurred at later time intervals. Similarly, relative RFD (i.e.%MVC{bullet operator}s-1) (RFDr) increased 33-56% at time intervals up to 70 ms from the onset of the contraction (P<0·05). It can be concluded that a short period of resistance training performed with concentric fast-velocity isokinetic muscle contractions is able to enhance RFD and RFDr obtained at the early phase of rising muscle force. © 2013 The Authors Clinical Physiology and Functional Imaging © 2013 Scandinavian Society of Clinical Physiology and Nuclear Medicine.
Keywords: Muscle adaptation; Muscle strength; Peak torque; Power; Quadriceps muscle; bicycle ergometer; biomechanics; controlled study; dynamometer; fast velocity resistance training; goniometer; human; isokinetic exercise; knee; knee function; male; muscle isometric contraction; muscle strength; normal human; priority journal; range of motion; rate of force development